MENINGKATKAN KETERAMPILAN MENULIS PUISI MELALUI TEKNIK AKROSTIK PADA SISWA KELAS IV SDN MANGGARAI 01 - Siti Naurah Laila Rasyidah; Juhana Sakmal; Endang M Kurnianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve poetry writing skills through the implementation of the acrostic technique among fourth-grade students of SDN Manggarai 01. The method employed in this study was Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles. Each cycle consisted of two meetings, involving 30 fourth-grade students of SDN Manggarai 01 in the 2025/2026 academic year. The research procedures included planning, action, observation, and reflection stages. Data analysis in this study was descriptive, consisting of qualitative analysis and numerical data, while data collection techniques included poetry writing tests, observation sheets, field notes, and documentation. The results of the study indicated an improvement in students’ poetry writing skills after the implementation of the acrostic technique, as shown by an increase in the percentage of mastery from 63% in Cycle I to 87% in Cycle II. Based on these findings, the acrostic technique can be used as an alternative learning strategy to support students in writing poetry, particularly at the elementary school level.